Tecendo uma análise sobre a atenção domiciliar no Sistema Único de Saúde - Ortiz, Bruna Maria Limeira Rodrigues (2017)
Since its birth in 1988, the Unified Health System has undergone constant and complex transformations, and although often contradictory, aim to achieve the consolidation of a universal health system, equanimous and integral health care. In this sense, home care has been increasingly linked to the possibility of responding to the demographic and epidemiological changes that are so pressing on the health system, relating to the rationalization of hospital beds, reducing healthcare costs for health systems And by a logic of care based on humanization. The objective of this study was to analyze the entry of the topic in the government agenda and the implementation of Home Care Services in Brazilian municipalities between years 2011 and 2015. The method used was based on the analysis of official documents and data, interviews with federal and Representative of society that were related to the formulation and implementation of the Home Care Services (SAD), as well as analysis of secondary data obtained through national information systems. The SADs, represented by the government program known as the "Better at Home Program", will have priority on the federal agenda beginning in 2011, articulating a broad agenda of mobilization and rapid rise. The habilitation and implementation of services varied between regions and states, with less impact in small municipalities and states such as Sergipe, Mato Grosso, Espirito Santo and Roraima. When analyzing the variables that may have influenced the effectiveness of SAD habilitation and implementation, treating as a dependent variable the habilitation and implantation of home care teams and selected indicators as independent variables, the representative findings were characterized by indicators: households, IDSUS and Gini. Although populational criteria are widely adopted mechanisms to support the direction of public policy, other indicators can contribute to analysis in order to promote equity in the distribution of home care and other public health policies in the SUS.